Peningkatan Literasi Digital Masyarakat RT 09 Kelurahan SAWAH LEBAR BARU Melalui Pelatihan Pemanfaatan Media Sosial Sebagai Sarana Promosi UMKM - Defri Wiranata; Andreas Pandiangan; Lia Hanifah; Cahya Rozalina; Nelsa Zelviona; Yoli Andi Rozzi (Universitas Dehasen Bengkulu, 2026)
Improving Digital Literacy of the Community in RT 09 Sawah Lebar Baru Village through a Community Service Program (KKN) by Dehasen University Bengkulu. The low level of digital literacy amidst rapid technological developments is a major challenge faced by the community, including in RT 09 Sawah Lebar Baru Village, Bengkulu City. The Community Service Program (Kuliah Kerja Nyata or KKN) by Dehasen University Bengkulu aimed to address this issue by providing a basic understanding of safe and productive digital technology usage, and raising awareness about the importance of digital security. The implementation methods included an initial survey to identify the level of understanding (which showed that most people had limited knowledge, difficulty distinguishing hoaxes, and that the elderly/housewives struggled with technology), followed by lectures, demonstrations, direct practice, and discussions. The program results showed a significant increase in the community's digital knowledge and skills. Participants are now able to practice correct smartphone usage, understand the importance of maintaining account security and personal data, and be more cautious about online fraud. Overall, the program successfully strengthened the relationship between the university and the community while helping the residents of RT 09 become better prepared to face the challenges of the digital era.